2014
DOI: 10.1002/cjce.22093
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbons – water phase equilibria using the CPA equation of state with a group contribution method

Abstract: It is proposed in this paper to extend the original group contribution method PPR78 to systems containing water, by combining it to the Cubic–Plus–Association (CPA) equation of state (EoS). Applying simple geometric combination rules, the binary interaction parameter kij(T) can be calculated from interaction parameters between hydrocarbon groups and water. This model, called the GC–PR–CPA is applied to predict hydrocarbons – water mutual solubilities over a wide temperature and pressure range, depending on ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 59 publications
2
18
0
Order By: Relevance
“…The phase equilibrium water compositions are shown in Figure 1 with experimental measurements from the literature. The water mole fractions of n-decane match well with the measurements, but those of toluene have deviations of ~20% (Note that using a cubic-plus-association EoS [46], which is compatible with PPR78, improves the phase equilibrium calculations). As a group contribution method, PPR78 yields phase equilibrium results with correct trends and tolerable errors.…”
Section: Physical Propertiessupporting
confidence: 58%
“…The phase equilibrium water compositions are shown in Figure 1 with experimental measurements from the literature. The water mole fractions of n-decane match well with the measurements, but those of toluene have deviations of ~20% (Note that using a cubic-plus-association EoS [46], which is compatible with PPR78, improves the phase equilibrium calculations). As a group contribution method, PPR78 yields phase equilibrium results with correct trends and tolerable errors.…”
Section: Physical Propertiessupporting
confidence: 58%
“…The parameters ( , , , , ) for pure water are obtained by adjusting to vapor pressure and saturated liquid density data correlated by NIST [38]. The water parameters obtained in this work and those obtained previously by Hajiw et al [23] and Wang et al [24,25] are reported in Table 4. As shown in Figure 2, the e-PR-CPA model can accurately describe the pure water VLE data, apart in the near critical region.…”
Section:  Pure Watermentioning
confidence: 81%
“…Some of the latter studies have correlated the experimental data by the Cubic equations attached by one 12 and two 11 system-specific, three system-and temperature-specific 18,19 and four systemspecific 20 binary adjustable parameters. In this respect, several recent researches [21][22][23][24][25][26][27][28][29][30] performing a modeling of phase equilibria in the water-aromatic compound systems using various approaches should be acknowledged as well. The last two studies present a significant interest in the context of the current investigation.…”
Section: Introductionmentioning
confidence: 99%